2020
DOI: 10.1007/s40544-019-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between friction coefficient and areal topography parameters for AISI 304 steel sliding against AISI 52100 steel

Abstract: Dry wear experiments provide an insight detail on how severely contacting surfaces change under unlubricated sliding condition. The theory of dry sliding wear is used for understanding mixed-lubrication regime in which asperity interactions play a significant role in controlling of the friction coefficient (f). The purpose of this work is to study the tribological behavior of AISI 304 steel in contact with AISI 52100 steel during wear. Both materials are used in rolling element bearings commanly. Experiments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…There is evidence of wear track on the disks that had a roughing WEDM condition, and the curve for the pin revealed a degradation that quickly overgrew. In 2 min of testing, the diameter of the pin footprint reached 70% of its final diameter compared to the diameter found at 40 min, similar to Prajapati et al [31] when studying pin-on disk of short duration. SEM images revealed that abrasive wear and plastic deformation processes are present in every surface configuration (see Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…There is evidence of wear track on the disks that had a roughing WEDM condition, and the curve for the pin revealed a degradation that quickly overgrew. In 2 min of testing, the diameter of the pin footprint reached 70% of its final diameter compared to the diameter found at 40 min, similar to Prajapati et al [31] when studying pin-on disk of short duration. SEM images revealed that abrasive wear and plastic deformation processes are present in every surface configuration (see Fig.…”
Section: Resultssupporting
confidence: 85%
“…The hardness values of the disks were 505 ± 13 HV. The disks were hardened and tempered to obtain similar hardness values than [31]. The surfaces of the disks were WEDM [15] (Novick AR 35 MA) by using two operational conditions: half of them in a finishing condition (t on = 5 μs; t off = 34 μs; T = 39 μs; f = 25.6 Hz; t on /T = 0.13; V = 4 V), and the other half in a roughing condition (t on = 50 μs; t off = 180 μs; T = 230 μs; f = 4.3 Hz; t on /T = 0.22; V = 6 V).…”
Section: Methodsmentioning
confidence: 99%
“…The wear particles grew into rolling cylinders and into larger aggregates, which took the form of flakes, creating a third-body layer and the macroscopic roughness. The monotonic decreasing in friction coefficient, monotonic or non-monotonic changes in surface roughness and other topographic features as well as gradual work hardening have also been reported during different types of tribopairs [354][355][356][357].…”
Section: Running-in and Surface Structure Evolutionmentioning
confidence: 92%
“…Among stainless steels (ASS), austenitic grades, and specially AISI 304 has the most used in bearings, chemical industries, and surgical and marine equipment ( Prajapati and Tiwari, 2021 ; khaleal et al., 2020 ). Although their excellent corrosion resistance, their low yield strength restricts applications in harsh environments and may necessitate searching for a suitable substitute ( Avilaa et al., 2020 ; Alabdullah et al., 2016 ; Moharana et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%